Use of the volatile trichodiene to reduce Fusarium head blight and trichothecene contamination in wheat. Issue 2 (2nd February 2021) - Taylor, Laurie; Gutierrez, Santiago; McCormick, Susan P.; Bakker, Matthew G.; Proctor, Robert H.; Teresi, Jennifer; Kurtzman, Ben; Hao, Guixia; Vaughan, Martha M.
Summary: Fusarium graminearum is the primary cause of Fusarium head blight (FHB), one of the most economically important diseases of wheat worldwide. FHB reduces yield and contaminates grain with the trichothecene mycotoxin deoxynivalenol (DON), which poses a risk to plant, human and animal health. The first committed step in trichothecene biosynthesis is formation of trichodiene (TD). The volatile nature of TD suggests that it could be a useful intra or interspecies signalling molecule, but little is known about the potential signalling role of TD during F. graminearum ‐wheat interactions. Previous work using a transgenic Trichoderma harzianum strain engineered to emit TD ( Th + TRI5 ) indicated that TD can function as a signal that can modulate pathogen virulence and host plant resistance. Herein, we demonstrate that Th + TRI5 has enhanced biocontrol activity against F. graminearum and reduced DON contamination by 66% and 70% in a moderately resistant and a susceptible cultivar, respectively. While Th + TRI5 volatiles significantly influenced the expression of the pathogenesis‐related 1 ( PR1 ) gene, the effect was dependent on cultivar. Th + TRI5 volatiles strongly reduced DON production in F. graminearum plate cultures and downregulated the expression of TRI genes. Finally, we confirm that TD fumigation reduced DON accumulation in a detached wheat head assay. Abstract : This study represents the first to demonstrate that trichodiene, the volatile intermediate of trichothecene biosynthesis, can regulate deoxynivalenol production. Trichoderma harzianum genetically engineered to emit trichodiene has increased biocontrol activity against Fusarium head blight resulting in 66–70% reduction in deoxynicalenol contamination.